(untitled) - Boss, Judith A. (New York, 2008)
This text addresses a variety of timely and interesting moral issues, providing background information and primary source selections for each issue presented. It includes a chapter on ethical theory and covers a broad range of ethical perspectives--among them virtue ethics (Aristotelian and Confucian), Buddhist and feminist care ethics, and the Rawlsian and communitarian approaches. This fourth edition includes a new section on Ethical Egoism and has been updated to include readings and case studies covering some of the most pressing issues of recent ethical debate, such as stem cell research, the Iraqi War, the effect of the U.S. Patriot Act on academic freedom, Military conscription, racial profiling of Arab-Americans, the conflict in Darfur, and more.
Keywords: Ethical problems,Luận đề đạo đức